2014
DOI: 10.1017/s0022215114002783
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of airway stenosis by radiofrequency coblation

Abstract: Radiofrequency coblation is an attractive alternative technique for the treatment of idiopathic or acquired airway stenosis in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Various methods of airway management have been described, but currently no gold standard exists . Jet ventilation has been described as the preferred technique despite a UK National Survey highlighting potential complications including pneumothorax, pneumomediastinum, surgical emphysema, hypoxia and death . High‐frequency jet ventilation delivered above the stenosis may be hazardous with small diameter stenoses, whilst some authors only recommend manual low‐frequency jet ventilation for emergencies or very short elective procedures …”
Section: Introductionmentioning
confidence: 99%
“…Various methods of airway management have been described, but currently no gold standard exists . Jet ventilation has been described as the preferred technique despite a UK National Survey highlighting potential complications including pneumothorax, pneumomediastinum, surgical emphysema, hypoxia and death . High‐frequency jet ventilation delivered above the stenosis may be hazardous with small diameter stenoses, whilst some authors only recommend manual low‐frequency jet ventilation for emergencies or very short elective procedures …”
Section: Introductionmentioning
confidence: 99%
“…However, more data is still needed to demonstrate the potential of coblation in managing airway stenosis, with only few reports up to now. Fastenberg et al [1] reported its use in six pediatric otolaryngologic cases with different airway pathologies and Chan et al [6] reported its use in adults with the airway stenosis less than 1 cm in length. This paper described tracheotomy-coblation in managing a 2 cm-long airway stenosis, and the result was satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ablation (PA) ablates the tissue precisely by a layer of plasma that results in breakage of molecular bonds with minimal heat dissipation, which reduces collateral thermal damage 5 . Its use has recently been attempted in the management of LTS but has not been popularized due to scarcity of evidence and long‐term follow‐up 6 , 7 . The current study was conducted to highlight the use of PA as a promising tool in the management of adult LTS.…”
mentioning
confidence: 99%
“…5 Its use has recently been attempted in the management of LTS but has not been popularized due to scarcity of evidence and long-term follow-up. 6,7 The current study was conducted to highlight the use of PA as a promising tool in the management of adult LTS.…”
mentioning
confidence: 99%